Automated Diagnosis of Canine Gastrointestinal Parasites Using Image Analysis - Sandra Valéria Inácio; Jancarlo Ferreira Gomes; Alexandre Xavier Falcão; Celso Tetsuo Nagase Suzuki; Walter Bertequini Nagata; Saulo Hudson Nery Loiola; Bianca Martins dos Santos; Felipe Augusto Soares; Stefani Laryssa Rosa; Carolina Beatriz Baptista; Graziella Borges Alves; Katia Denise Saraiva Bresciani (Pathogens, 2020)
Because canine intestinal parasites are considered cosmopolitan, they carry significant zoonotic potential to public health. These etiological agents are routinely diagnosed using microscopic examination commonly used because of its low cost, simple execution, and direct evidence. However, there are reports in the literature on the poor performance of this test due to low to moderate sensitivity resulting from frequent errors, procedures and interpretation. Therefore, to improve the diagnostic efficiency of microscopic examination in veterinary medicine, we developed and evaluated a unique new protocol. This system was tested in a study involving four genera of highly prevalent canine intestinal parasites in an endemic region in São Paulo state, Brazil. Fecal samples from 104 animals were collected for this research. The new protocol had a significantly higher (p < 0.0001) number of positive cases on image data, including parasites and impurities, and was elaborate to test them with the TF-GII/Dog technique, with a moderate agreement and Kappa index of 0.7636. We concluded that the new Prototic Coproparasitological Test for Dogs (PC-Test Dog) allowed a better visualization of the parasitic structures and showed a favorable result for the diagnosis of intestinal parasites in dogs.